Aphrodite Pandemos at Naukratis Revisited: The Goddess and her Civic Function in the Context of an Archaic Emporion - Daniels, Megan J. (Journal of Greek Archaeology, 2018)
Aphrodite Pandemos (‘all the people’) is a curious character in Greek religious thought: distinguished from her older and loftier counterpart, Aphrodite Ourania (‘heavenly’), through her linkage to more ‘common’ forms of love, namely heterosexual union, she was also associated with civic cohesion and the semi-mythical origins of the Athenian city-state. Yet our earliest evidence for the worship of Aphrodite Pandemos comes not from Athens but from Naukratis – a settlement nestled in the Nile Delta, resulting from a joint endeavour by a number of Greek city-states in the late 7th century BC under the Saite pharaohs. Previous scholarly considerations of Aphrodite Pandemos at Naukratis downplayed her civic associations largely based on the ambiguous political status of Naukratis, and instead concentrated on her role as a type of ‘general access’ goddess to the mixed communities commonly found in trading settlements.